Relational Analysis between Profile Characteristics and Extent of Conflict among Agricultural Officers - P.Venkata Rao,; S. Neelaveni,; P. Punna Rao, (Journal of Agricultural Extension Management, 2015)
This study was taken up to analyse the relationship of profile characteristics of Agricultural Officers with the extent of conflict and to know the profile characteristics which influence the extent of conflict faced by Agricultural Officers. The study revealed that perception of work load and span of control were positively and significantly related with extent of conflict. The other variables that were negatively and significantly related include coordination, decision-making ability, attitude towards the organization, empathy and job experience. All the variables taken for the study together explained a significant 45.16 pet cent of variation in the extent of conflict faced by Agricultural Officers.